PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN BERKUNJUNG KE LOKASI WISATA PULAU PENYENGAT TANJUNGPINANG - Eka Kurnia Saputra (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine whether consumer behavior influences the decision to visit Penyengat Island tourist site. This type of research is quantitative associative with a research sample of 100 domestic and foreign tourists visiting Penyengat Island tourist site. The sampling technique used is based on the Slovin technique. The type of data used in this study is to use primary data and secondary data while the data analysis technique used is a simple linear regression test by testing the hypothesis. The results showed that the result of the t value is 2.036> t Table 1.984 and the significance value (Sig.) 0.044 <0.05. So it can be concluded that the variable consumer behavior affects the decision to visit Penyengat Island tourism. In this case, the influence of consumer behavior on the decision to visit Penyengat Island tourist location is needed in order to continue to increase the number of visitors to tourist sites on Penyengat Island while adhering to the covid-19 health protocol.